2021
DOI: 10.1007/s10856-020-06477-4
|View full text |Cite
|
Sign up to set email alerts
|

Tribological, biocompatibility, and antibiofilm properties of tungsten–germanium coating using magnetron sputtering

Abstract: In this study, borosilicate glass and 316 L stainless steel were coated with germanium (Ge) and tungsten (W) metals using the Magnetron Sputtering System. Surface structural, mechanical, and tribological properties of uncoated and coated samples were examined using SEM, X-ray diffraction (XRD), energy-dispersive spectroscopy, and tribometer. The XRD results showed that WGe2 chemical compound observed in (110) crystalline phase and exhibited a dense structure. According to the tribological analyses, the adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Previous studies showed that DLC coatings had superior biocompatibility and cell attachment properties in several cell line such as osteoblast, fibroblast, and keratinocytes cell cultures 40–42 . Moreover, geranium based surface modifications were claimed that they have biocompatible properties and these materials did not stimulate toxic features for cell cultures 37,43,44 . In parallel with the literature, DLC–Ge coating supported cell growth and attachment in a favorable manner that cell survival ratio was analyzed to have similar properties to (−) Control with 95% cell viability rate (Figure 3).…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…Previous studies showed that DLC coatings had superior biocompatibility and cell attachment properties in several cell line such as osteoblast, fibroblast, and keratinocytes cell cultures 40–42 . Moreover, geranium based surface modifications were claimed that they have biocompatible properties and these materials did not stimulate toxic features for cell cultures 37,43,44 . In parallel with the literature, DLC–Ge coating supported cell growth and attachment in a favorable manner that cell survival ratio was analyzed to have similar properties to (−) Control with 95% cell viability rate (Figure 3).…”
Section: Resultsmentioning
confidence: 66%
“…[40][41][42] Moreover, geranium based surface modifications were claimed that they have biocompatible properties and these materials did not stimulate toxic features for cell cultures. 37,43,44 In parallel with the literature, DLC-Ge coating supported cell growth and attachment in a favorable manner that cell survival ratio was analyzed to have similar properties to (À) Control with 95% cell viability rate (Figure 3). After 24 h of seeding, fibroblast cell culture spread was found favorable on the GE-DLC coating compared to uncoated borosilicate glass surface ([+] Control) which was investigated by using Hoechst 33258 fluorescent staining (Figure 4).…”
Section: Structural and Morphological Characterizationmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition to the antibacterial, antitumor, and osseointegration capabilities of titanium implants—which are the most important in the field of orthopedics—the better biocompatibility of titanium implants is also an indispensable characteristic. RF magnetron sputtering, plasma spraying, and other technologies also play an important role in the preparation of titanium implants; in some reports, achievements have also been made in enhancing the biocompatibility of titanium implants [ 123 , 124 , 125 , 126 ]. In summary, in orthopedic clinics, in order to meet the needs of orthopedics, the processed titanium-based implants should have good physical properties, including elastic modulus, fatigue resistance, etc.…”
Section: Discussionmentioning
confidence: 99%